Coastal adaptations on the eastern seaboard of South Africa during the Pleistocene and Holocene? Current evidence and future perspectives from archaeology and marine geology - Will, Manuel; Bader, Gregor D.; Sommer, Christian; Cooper, Andrew; Green, Andrew (Frontiers in Earth Science, 2022)
The use of marine resources and the settlement of coastal settlements may have influenced the bio-cultural evolution and dispersal of Pleistocene Homo sapiens in Africa. In order to test such scenarios, however, we require evidence for these behaviours deriving from an expanded spatio-temporal archaeological record. The Stone Age of South Africa documents the richest and longest record of coastal adaptations. In contrast to abundant evidence of coastal sites on the western and southern seaboard, the eastern Indian Ocean coast has not played a role in recent discussions. Considering the important and well-known Middle and Later Stone Age (MSA/LSA) record from inland sites of KwaZulu-Natal (KZN), this region may be an underappreciated area for further study. Here we provide a systematic overview of marine resource use and the settlement of coastal landscapes during the Late Pleistocene and Holocene in KZN. For the first time, we contextualize these archaeological findings with a review and new data on the changing marine and coastal geomorphology in the context of GIS modelling and offshore marine geophysical investigations. Our review finds evidence for long-term dietary and non-dietary use of marine resources during the MSA and LSA from a few stratified sites, with many more surface occurrences particularly for the MSA along the modern KZN coastline indicating human habitation. Comparisons to other areas of South Africa, GIS modelling and geological considerations suggest that current data on the eastern seaboard is not reflective of the original extent and nature of the consumption of marine foods and settlement of coastal landscapes. By contextualizing the biased and patchy MSA and LSA record with results on the dynamic marine and coastal geomorphology of KZN, we develop productive lines of future studies to assess open questions on potential coastal adaptations in this region. These research strategies include the identification of areas with high potential for finding new sites within a 10 km transect along the current coastline as well as dedicated off-shore projects including underwater archaeology aided by new marine geological work in the southwest Indian Ocean.